The Energy Produced By 150 Watt Monocrystalline Solar Panels In Metro City - Muhammad Barkah Salim; Novita Intan Kusuma; Nyoto Suseno (JIPF (Jurnal Ilmu Pendidikan Fisika), 2020)
Researchers have conducted research on the energy produced by 150 watt solar panels in the city of metro. This research was conducted because many solar panels have been made, but it has not yet been identified how much energy is actually produced. In addition, to find out whether the city of metro is feasible to use solar panels. The purpose of this study was to determine the energy produced by 150 watt solar panels in the city of metro. The research method used is experimental research. Researchers conducted for five days from 08.00 AM to 04.00 PM. After doing the research, it was found that the energy that could be produced in the solar panel in one day was 876,507 joule. The value of the effectiveness of solar panels in the city of metro has a value of 100% with criteria for proper use.